A new breeding colony of the Wedge-rumped Storm-Petrel (Hydrobates tethys kelsalli, Lowe 1925) on Foca Island, extreme Northwestern Peru - García-Olaechea, Diego Alonso (2020)
Breeding colonies of Storm-petrels (family Hydrobatidae) are poorly known and can be difficult to find because they typically nest on islands in crevices and burrows inside caves. In the past decade, some breeding locations of the Wedge-rumped Storm-petrel (Hydrobates tethys kelsalli) have been reported on islands off central Peru and northern Chile. Here we report the northernmost breeding colony of this subspecies from Isla Foca, northern of Peru. In April 2006 we found 28 nests, of which 46% had chicks and 54% had eggs. Nests consisted of small holes in the rock with no nest material used for construction. Nesting season coincided with that of other reproductive zones found on the Peruvian coast. These results contribute to the knowledge of the distribution of reproductive colonies of this subspecies on the Peruvian coast.